2020
DOI: 10.1093/gji/ggaa597
|View full text |Cite
|
Sign up to set email alerts
|

Temperature distribution in a permafrost-affected rock ridge from conductivity and induced polarization tomography

Abstract: Summary Knowledge of the thermal state of steep alpine rock faces is crucial to assess potential geohazards associated with the degradation of permafrost. Temperature measurements at the rock surface or in boreholes are however expensive, invasive, and provide spatially-limited information. Electrical conductivity and induced polarization tomography can detect permafrost. We test here a recently developed petrophysical model based on the use of an exponential freezing curve applied to both elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The air temperature anomaly was calculated in comparison to the 1961–1990 mean air temperature used to derive the MARST map (Section 2), and from the daily air temperature recorded by Météo France at Chamonix (1,042 m a.s.l.) since 1993 (beginning of hourly air temperature records), similarly to Magnin et al 47 Despite its low elevation compared to most rockfall detachment zones, the Chamonix weather station was chosen rather than a high‐elevated station because of the high quality of the time series (thoroughly checked by Météo France to avoid measurement errors and no gap) and because this air temperature time series is the longest and the best correlated with measured surface temperature in the MBM (see for example the study from Duvillard et al 48 for correlation). Such approach to reconstruct RST time series was also used by Magnin et al 47 to simulate the long‐term evolution of rock wall temperature at the Aiguille du Midi, and was validated against borehole temperature measurements (maximum temperature difference of 0.2°C at 10 m depth over the 2010–2015 period for annual values and 0.5°C for daily values).…”
Section: Methodsmentioning
confidence: 99%
“…The air temperature anomaly was calculated in comparison to the 1961–1990 mean air temperature used to derive the MARST map (Section 2), and from the daily air temperature recorded by Météo France at Chamonix (1,042 m a.s.l.) since 1993 (beginning of hourly air temperature records), similarly to Magnin et al 47 Despite its low elevation compared to most rockfall detachment zones, the Chamonix weather station was chosen rather than a high‐elevated station because of the high quality of the time series (thoroughly checked by Météo France to avoid measurement errors and no gap) and because this air temperature time series is the longest and the best correlated with measured surface temperature in the MBM (see for example the study from Duvillard et al 48 for correlation). Such approach to reconstruct RST time series was also used by Magnin et al 47 to simulate the long‐term evolution of rock wall temperature at the Aiguille du Midi, and was validated against borehole temperature measurements (maximum temperature difference of 0.2°C at 10 m depth over the 2010–2015 period for annual values and 0.5°C for daily values).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 13 illustrates the variation of the electrical conductivity as a function of temperature measured by Duvillard et al (2018Duvillard et al ( , 2021 for granite and rock glacier. Values of ϕ and 𝐴𝐴 𝐴𝐴𝑤𝑤 for those samples are reported by Duvillard et al (2018Duvillard et al ( , 2021 and shown in Table 5. The value of C u can be estimated using Equation 6and is shown in Table 5.…”
Section: Duvillard Et Al (2018 2021)mentioning
confidence: 99%
“…The electrical conductivity is highly related to the basic physical properties of frozen porous medium such as porosity, liquid water content, or hydraulic conductivity. Duvillard et al (2018Duvillard et al ( , 2021 and Coperey, Revil, Abdulsamad et al (2019), characterized the spatial distribution of frozen and unfrozen zones from the electrical conductivity contrasts between ice and pore water, and determined the relationship between electrical conductivity and temperature in the frozen state using laboratory IP experiments. Results revealed that the above-mentioned geophysical methods can be applied to the quantitative and qualitative study of soil hydrology at freezing temperatures.…”
mentioning
confidence: 99%
“…Therefore, they have become the key approach for disaster monitoring and environmental investigation. Additionally, electromagnetic methods are effective for frozen soil and glacier monitoring, pollution detection, engineering practices, and hydrogeological exploration [21,22]. The research above shows that the Red Mudstone is easy to distinguish from bedrock, and the causes of Red Mudstone Landslide in different study areas are closely related to the surrounding environment [23].…”
Section: Introductionmentioning
confidence: 99%